2022
DOI: 10.1038/s41419-022-04568-4
|View full text |Cite
|
Sign up to set email alerts
|

ARL6IP5 reduces cisplatin-resistance by suppressing DNA repair and promoting apoptosis pathways in ovarian carcinoma

Abstract: Ovarian carcinoma (OC) is the most lethal gynecological malignancy due to frequent recurrence resulting from cisplatin-resistance. ARL6IP5 is a novel gene implicated to suppress cisplatin-resistance by activating apoptosis and inhibiting DNA repair through XRCC1 and PARP1. We investigated the clinicopathological and prognostic significance of the immunohistochemical ARL6IP5 expression on 79 post-chemotherapy OC patient tissue samples; in vitro, the effect of ARL6IP5 overexpression (OE) and knockdown (KD) on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We found that cisplatin induced morphological changes and reduced SKOV-3 cell viability in a dose-dependent manner, and its IC50 was approximately 20 µM ( Figure S1, Supplementary Materials ). Based on this information and previous studies reporting that cisplatin at 20 µM efficiently induces DNA damage and apoptotic death in SKOV-3 cell lines [ 33 , 34 , 35 ], we thus utilized cisplatin at 20 µM in our study. We demonstrated that cisplatin alone could significantly decrease the cell viability to about 90% and 50% after 24 h and 48 h, respectively ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…We found that cisplatin induced morphological changes and reduced SKOV-3 cell viability in a dose-dependent manner, and its IC50 was approximately 20 µM ( Figure S1, Supplementary Materials ). Based on this information and previous studies reporting that cisplatin at 20 µM efficiently induces DNA damage and apoptotic death in SKOV-3 cell lines [ 33 , 34 , 35 ], we thus utilized cisplatin at 20 µM in our study. We demonstrated that cisplatin alone could significantly decrease the cell viability to about 90% and 50% after 24 h and 48 h, respectively ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…In neurodegenerative disease, Siddique et al demonstrated that ARL6IP5 can reduce the burden of α-synuclein aggregates and improve cell survival in a cellular model of Parkinson’s disease by inducing autophagy through the prevention of ubiquitination and degradation of autophagy-related 12 protein [ 24 ]. Nevertheless, ARL6IP5 can also suppress DNA repair and promote apoptosis pathways in ovarian carcinoma cells [ 25 ]. ARL6IP5 has been reported to be expressed in the kidney and is a potential causal candidate contributing to pleiotropic pathways between CKD and hyperuricemia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ADP ribosylation factors like GTPase 6 interacting protein 5 ( ARL6IP5 ), a kind of microtubule-associated protein, can reduce the resistance to cisplatin in OC cells by suppressing DNA repair protein and promoting apoptosis. In addition, ARL6IP5 also acts as a significant prognostic factor and tumor suppressor in OC [ 69 ]. Forkhead box protein O1 ( FOXO1 ) is the downstream target of PI3K/Akt signaling pathway, which is upregulated in EOC tissues, and its overexpression predicts the poor prognosis.…”
Section: Discussionmentioning
confidence: 99%